1979
DOI: 10.1111/j.1365-2605.1979.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Androgens on the Kidney of Female Mice: Strain Differences in the DNA and β‐Glucuronidase Responses

Abstract: The anabolic effects of testosterone on kidneys from two strains of female mice were studied over a course of 25 days. The A/J and C57BL/6J strains were selected because they carry regulatory alleles Gura and Gurb which determine rapid and slow induction of β‐glucuronidase, respectively. (A major goal of this study was to determine whether these mouse strains have other differences in their responses to testosterone). The wet weight, dry weight and total protein content of the kidneys of both strains increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Independently from the observed range, however, it is characteristic for all three groups that animals with higher blood pres sures had a higher daily yGT excretion rate than those with a less expressed hypertension ( fig-O-As shown in table I testosterone affected not only the output of yGT, but also that of NAG: with ~ 8 U/g creatinine castrates ex creted the same amount as untreated female rats [see 17], i.e., far less than hypertensive males or hypertensive, testosterone-substi tuted castrates. This finding is in good accor dance with the results of Koenig et al [8] and Mills et al [20] who showed that in the absence of testosterone the secretion rate of lysosomal hydrolases is generally reduced. Furthermore, there is one special circum stance of the NAG output which deserves consideration: the existence of a positive cor relation between the NAG output and the HP content of the kidneys of hypertensive male rats and testosterone-substituted castrates ( fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Independently from the observed range, however, it is characteristic for all three groups that animals with higher blood pres sures had a higher daily yGT excretion rate than those with a less expressed hypertension ( fig-O-As shown in table I testosterone affected not only the output of yGT, but also that of NAG: with ~ 8 U/g creatinine castrates ex creted the same amount as untreated female rats [see 17], i.e., far less than hypertensive males or hypertensive, testosterone-substi tuted castrates. This finding is in good accor dance with the results of Koenig et al [8] and Mills et al [20] who showed that in the absence of testosterone the secretion rate of lysosomal hydrolases is generally reduced. Furthermore, there is one special circum stance of the NAG output which deserves consideration: the existence of a positive cor relation between the NAG output and the HP content of the kidneys of hypertensive male rats and testosterone-substituted castrates ( fig.…”
Section: Discussionsupporting
confidence: 79%
“…Sex differences in the enzyme architecture of the rat kidney have been known for a long time [1], Especially the effect of the male sex ual hormone on the histology of the kidney and on the activity of certain enzymes has been extensively studied [7,8,20,22,23,25]. Thus, it was shown that the administration of testosterone causes renal hypertrophy and in creases the protein content of the kidney [2,6,9,24], However, nothing is known about the cause of sex differences in the urinary output of enzymes, e.g., yGT.…”
mentioning
confidence: 99%
“…This renal enlargement was secondary to both cellular hyperplasia and hypertrophy, since in males there was a greater increase in cell number and protein concentration. In agreement with the findings of Kochakian (1975), Bardin et al (1978 ) and Mills et al (1979), the present results show that the increase in kidney weight in adult females treated with testosterone was secondary to cellular hypertrophy rather than hyperplasia. The kidney weight of these testosterone-treated adult female mice remained smaller than that of males and this difference could be attributed to the reduced basal number ofcells which was not increased by androgen treatment.…”
Section: Responsiveness Of the Kidney To Testosterone In Adult Micesupporting
confidence: 95%
“…In mice, but not in all species, renal size is reduced by orchidectomy, while administration of testosterone stimulates a marked response of the kidney as indicated by an increase in the synthesis of nucleic acids and protein (Selye, 1939;Kochakian, 1959Kochakian, , 1975Mills, Mills, Yurkiewicz & Bardin, 1979). The sex-related difference in kidney size has been attributed to the androgenic status of the animal, and the mouse kidney has become an important tissue for studying the mechanism of androgen action (Bardin, Bullock, Sherins et al 1973;Bardin, Brown, Mills et al 1978 ).…”
Section: Introductionmentioning
confidence: 92%
“…Testosterone administration markedly increases the activity of OrnDCase and other proteins in mouse kidney (5,6,14,15,(33)(34)(35) and produces cellular hypertrophy rather than hyperplasia (35). The induction requires functional androgen receptors and is seen as early as a few hours after hormone administration (5,34).…”
Section: Discussionmentioning
confidence: 99%